Basel Accords, Bank Capital and Portfolio Risk Behavior - Riaz, Samina (Cambridge Scholars Publisher, 2019)
With the endorsement of the Basel III contracts on the supervision of the banking industry, management of capital buffers throughout the business cycle have attained crucial importance for the reinforcement of financial stability in the banking system. This book departs from previous studies through its focus on developing countries and their assessment of the behavior of capital and risk.